2008
DOI: 10.1364/oe.16.006486
|View full text |Cite
|
Sign up to set email alerts
|

Measuring retinal contributions to the optical Stiles-Crawford effect with optical coherence tomography

Abstract: The directional component of the retinal reflection, i.e., the optical Stiles-Crawford effect (SCE), is well established to result from the waveguiding property of photoreceptors. Considerable uncertainty, however, remains as to which retinal reflections are waveguided and thus contribute. To this end we have developed a retina camera based on spectral-domain optical coherence tomography (SD-OCT) that axially resolves (~5 μm) these reflections and permits a direct investigation of the SCE origin at near infrar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
113
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(126 citation statements)
references
References 37 publications
8
113
0
Order By: Relevance
“…It is well known that the cones have relatively narrow angular reflectance functions, returning much more of the incident light towards a point near the center of the pupil than towards points farther away from the center. This phenomenon is closely related to the Stiles-Crawford effect [9,[27][28][29], which describes the variation in the visual effectiveness of light entering through different locations in the pupil. In this study, we used a commercial AO flood-illuminated camera; with the method developed for processing of these images, which is largely automated, it is possible to establish an analysis routine that can be applied in clinics as part of a research procedure for assessing the health of the cone mosaic in patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that the cones have relatively narrow angular reflectance functions, returning much more of the incident light towards a point near the center of the pupil than towards points farther away from the center. This phenomenon is closely related to the Stiles-Crawford effect [9,[27][28][29], which describes the variation in the visual effectiveness of light entering through different locations in the pupil. In this study, we used a commercial AO flood-illuminated camera; with the method developed for processing of these images, which is largely automated, it is possible to establish an analysis routine that can be applied in clinics as part of a research procedure for assessing the health of the cone mosaic in patients.…”
Section: Discussionmentioning
confidence: 99%
“…Investigation of the cone reflectance in different retinal areas and over long time periods using an AO flood illumination camera is therefore lacking in the literature. It has already been observed that the position of the light source in an AO flood illumination system has an influence on the reflectance of the cone mosaic [9,24,[27][28][29], and this property has been used to study the angular tuning of single cones [15,28,30]. As the performance of the most commonly used cone detection algorithms depends on the quality of the images to which they are applied [31], it is also possible that the position of the light source itself affects not only the reflectance of the cones but also their detection and the subsequent estimation of the mosaic metrics.…”
Section: Introductionmentioning
confidence: 99%
“…This outcome may be explained by StilesCrawford effect that points out the directional sensitivity of the cone receptors. [15][16][17] The visual system has reduced sensitivity to light rays that are not concordant with the direction of the photoreceptors. [15][16][17] It was reported that when the integrity and orientation of the photoreceptors is disturbed by edema or traction, directional light sensitivity of the cones decline.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] The visual system has reduced sensitivity to light rays that are not concordant with the direction of the photoreceptors. [15][16][17] It was reported that when the integrity and orientation of the photoreceptors is disturbed by edema or traction, directional light sensitivity of the cones decline. 16,18 According to us, since the foveal architecture was improved postoperatively, the directional sensitivity of the photoreceptors increased, and the visual acuity gain occurred in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…6 with constant PMT gain, we recorded the mean relative photoreceptor intensity values presented in Table 5 below, that suggest an SCE described by lower ρ values than those published in the literature. This could be explained by the fact that the AOSLO images are focused on the reflections from the inner-outer segment interface, which according to the work by Gao et al [49] are less directional than those from the posterior surface of the photoreceptor outer segments. As a consequence of the difference in SCE between rods and cones, the ratio of cone to rod signal decreases as ε increases (see Table 6 ).…”
Section: Photoreceptor Mosaic At 10° Temporalmentioning
confidence: 99%